NOKIA, THE LOST SIGNALS - Syeda Umme, Sadia; Ahmed Amer, Adil; Diaa, Al Daqqaq (INTI International University, 2023)
The decline of Nokia, formerly a prominent player in the mobile phone business, signifies a substantial downfall resulting from the company's failure to adjust to the swift advancements in the smartphone market. Nokia, although initially successful with its robust and reliable mobile devices, failed to accurately predict and successfully address the emergence of touchscreen smartphones, which were spearheaded by competitors such as Apple and Samsung. The antiquated Symbian operating system, employed in previous iterations of Nokia phones, demonstrated inadequacy in comparison to contemporary platforms like iOS and Android. Nokia formed a strategic alliance with Microsoft in 2011, with the aim of recovering its market share. As part of this collaboration, Nokia decided to use the Windows Phone platform for its handsets. Nevertheless, this approach proved ineffective in turning around the company's financial situation. Nokia's lack of adaptability, inability to keep up with industry changes in terms of innovation, and strategic errors ultimately resulted in its financial difficulties. Microsoft purchased Nokia's Devices and Services division in 2014, effectively ending Nokia's previous dominance in the mobile phone manufacturing industry. The downfall of Nokia serves as a warning example of the negative outcomes that arise from being too comfortable and the urgent need for enterprises to quickly adjust in rapidly changing technology environments